Building technological pedagogical content knowledge through didactical design research - Atikah Sari (xxxx-xxxx, 2023)
This study aims to gain an in-depth understanding of how 15 elementary school teachers in a professional learning community demonstrate how to build their technological pedagogical content knowledge. The qualitative method used is Didactical Design Research. Data collection uses triangulation techniques, namely document studies, observations and interviews. The results of the study show that studying in a professional learning community will make it easier for teachers to master technology so that it can make it easier for them to plan, implement and assess learning. It was also revealed that the teacher's teaching practice was in line with the plan that had been prepared beforehand. Based on the implementation of professional teacher learning activities, it can be concluded that the teacher's knowledge and skills in teaching develop very well, can further develop meaningful learning activities, and can better master student characteristics. In addition, students can be more independent and really help students in higher order thinking.